Batee Iliek Tourism Development Model - Nazaruddin, Nazaruddin; Yani, Ahmad; Aisyah, Ti; Rahmi, Yulia (International Journal of Public Administration Studies, 2021)
Batee Iliek Tourism Object Development Model in Bireuen Regency which is nature tourism for the welfare of the community by developing objects or attractions, accessibility, amenities, supporting facilities, and institutions through government policies. The aim is to increase income and better economic development and provide job opportunities for the Batee Iliek community in Bireuen Regency and increase national income. The methodology used in this study uses a qualitative methodology and this study aims to obtain an overview of the Batee Iliek Tourism Object Development Model in Bireuen Regency. The results showed that the government and the community played a role in the tourism development program in Batee Iliek through the development of facilities, the development of tourist attractions, increasing the security of village tourist attractions and the development of cultural diversity in the area. The solutions given by the government are to provide facilities such as parking lots, bathrooms, and prayer rooms. By creating a diversity or regional characteristic, such as introducing Acehnese culture. introducing Acehnese cuisine, and selling unique bags with Acehnese carvings can attract visitors.